Unveiling the Current Internalization of Reflective Practice Activities in Worldwide Second Language Educational Contexts - Wijaya, Kristian Florensio (Journal of Education, Language Innovation, and Applied Linguistics, 2025)
Enhancing investment in globalized second language learning can be achieved through the continuous professional development of EFL teachers. Previous research suggests that significant growth in professional development occurs when accompanied by reflective practice activities. These activities enable educators to critically assess their teaching practices, leading to improved learning outcomes for language learners. This small-scale library study aimed to explore the current implementation of reflective practice in second language education worldwide. A thematic analysis approach was employed to analyze findings from previous studies on reflective practices. This method allowed for the categorization of key themes, ensuring a comprehensive understanding of reflective practice's impact on language teaching. To enhance the reliability of the findings, 25 reflective practice studies published in national and international journals were selected. The identified themes provide insights into how second-language educators can design more effective learning materials and foster transformative learning experiences. By integrating reflective practices, EFL teachers can refine their instructional strategies, ultimately contributing to the advancement of second language education.Keywords: Library study; professional development; reflective practice; second language learning; thematic analysis.